Silent Life and Silent Language : The Inner Life of a Mute in an Institution for the Deaf - Farlow, Kate M. (Book collections on Project MUSE., 2018)
"Presents a fictionalized account of life at a Midwestern residential school for deaf students in the years following the Civil war. Based on the experiences of the author who became deaf at the age of nine and entered a residential school when she was twelve"--